Themistius' paraphrase of Aristotle's Metaphysics 12 : a critical Hebrew-Arabic edition of the surviving textual evidence, with an introduction, preliminary studies, and a commentary - Themistius (Aristoteles Semitico-latinus ;, 2019)
"Themistius' (4th century) paraphrase of Aristotle's Metaphysics 12 is the earliest surviving complete account of this seminal work. Despite leaving no identifiable mark in Late Antiquity, Themistius' paraphrase played a dramatic role in shaping the metaphysical landscape of Medieval Arabic and Hebrew philosophy and theology. Lost in Greek, and only partially surviving in Arabic, its earliest full version is in the form of a 13th century Hebrew translation. In this volume, Yoav Meyrav offers a new critical edition of the Hebrew translation and the Arabic fragments of Themistius' paraphrase, accompanied by detailed philological and philosophical analyses. In doing so, he provides a solid foundation for the study of one of the most important texts in the history of Aristotelian metaphysics"--